Validation of Malay Brief Pain Inventory Questionnaire to Measure Cancer Pain - Aisyaturridha, A (Penerbit Universiti Sains Malaysia, 2005)
PURPOSE: This study was conducted to translate and validate the Brief Pain Inventory (BPI) questionnaire in the Malay language. The psychometric properties in terms of construct and concurrent validity of the Malay version of BPI were evaluated. The internal consistency and test-retest stability were also evaluated. METHODOLOGY: The original version of BPI was translated into a Malay version by the standard procedure and piloted among 35 cancer patients with pain. A total of 113 (95.0%) agreed to participate in this study out of 119 eligible patients with an age ranging from 18 to 76 years. They were interviewed between August and November 2004 for the main study to evaluate the psychometric properties of Malay version of BPI. RESULTS: The pain intensity items demonstrated high loading with a factor whereas the pain interference items were loaded on the other factor in factor analysis. Two factors explained 62% of the variance. With Karnofsky Performance Scale (KPS), pain intensity scale had a moderate negative (Pearson’s) correlation (r=−0.520, p<0.001) and pain interference scale had a good negative correlation (r=−0.732, p<0.001), showing an appropriate concurrent validity. The coefficient alpha of both scales demonstrated a good internal consistency of the items. The intraclass correlation coefficient for the test-retest stability was 0.61 for the pain intensity scale and 0.88 for the pain interference scale. CONCLUSION: Overall, the Malay version of the BPI is a reliable and valid instrument for cancer pain assessment and it is comparable with the original version of the BPI in terms of structure and psychometric properties.